Reality television programs in Malaysia : a dream come true? - Moy, Tow Yoon *; Garma, Romana (Sunway University College, 2006)
Reality television programs have changed the media landscape drastically since the turn of the millennium. Owing to its interactive nature, reality television has become a highly marketable advertising vehicle. In view of its rising popularity and potential in marketing, the influence of these programs is of public interest. This study examines what motivates the viewers in Malaysia to watch reality television programs. Using factor analysis, five motivation factors were extracted: suspense; personal identity and social interaction; engaging?entertaining; romance or attractiveness of contestants; sensation seeking. Three MANOVA models were used to explore the relationship between group differences due to gender, age, education background and the composite of the five motivational factors. Significant multivariate effects were found for all the three models considered. Univariate effects were also found for three of the factors, revealing some interesting findings of those who are fascinated by reality television programs in Malaysia.